Dinamika War of Position dalam Pengembangan Wisata Syariah di Pulau Santen Banyuwangi (Dynamics of War of Position in the Development of Sharia Tourism in Santen Island Banyuwangi) - Zelika, Yunda; Ganefo, Akhmad (Laboratorium Sosiologi FISIP Universitas Jember, 2020)
By narrating the development of sharia tourism, this article would like to explore the dynamics of the war of position practice between the Banyuwangi Culture and Tourism Office, TNI, and the Santen Island supervisory community group. It is based on the cracking of social capital in cooperation between the three entities. This issue is based on the orientation of different political-economic interests in each actor in sharia tourism practices. Therefore it is interesting to examine how the formation of the war of position conducted between the three entities in the sharia tourism floating discourse? In this study, data and information were obtained from an ethnographic approach through participant observation, interviews, and documentation. The data and information collected were then analyzed using the Gramscian perspective on hegemony and the concept of war position on the development of sharia tourism. The results showed a conflict of interest between the Culture and Tourism Office, TNI, and the Santen Island supervisory community group to achieve political economy orientation. It appears and represents the complexity of the problem of developing sharia tourism that has never been shown before. Keywords: Sharia Tourism, Political Interests, Position War Dengan menarasikan pengembangan wisata syariah, artikel ini hendak mengeksplorasi dinamika praktik perang posisi (war of position) diantara Dinas Kebudayaan dan Pariwisata Banyuwangi, TNI Banyuwangi, dan kelompok masyarakat pengawas Pulau Santen. Hal ini didasari oleh retaknya modal sosial dalam kerjasama diantara ketiga entitas tersebut. Persoalan ini didasari orientasi kepentingan ekonomi politik yang berbeda pada masing-masing entitas dalam praktik wisata syariah. Oleh karena itu menarik untuk diteliti bagaimanakah formasi perang posisi yang dilakukan diantara ketiga entitas tersebut dalam wacana pengambangan wisata syariah? Dalam penelitian ini, data dan informasi diperoleh dari pendekatan etnografi melalui observasi partisipan, wawancara, dan dokumentasi. Data dan informasi yang didapat kemudian dianalisis dengan menggunakan perspektif Gramscian tentang hegemoni dan perang posisi pada pengembangan wisata syariah. Hasil penelitian menunjukkan adanya benturan kepentingan diantara Dinas Kebudayaan dan Pariwisata, TNI Banyuwangi, dan kelompok masyarakat pengawas Pulau Santen untuk meraih orientasi ekonomi politik. Hal tersebut tampil dan merepresentasikan kompleksitas persoalan pengembangan wisata syariah yang tidak pernah ditampilkan sebelumnya. Kata kunci: Wisata Syariah, Politik Kepentingan, Perang Posisi